A digital photograph study evaluating facial taperness and square face perception of Taiwanese females. Issue 3 (3rd March 2021) - Wu, Tzu-Ying; Chou, Chein-Yu; Liang, Yu-Ming; Chang, Kuo-Wei; Wu, Cheng-Hsien
Abstract : Background: This study assessed the perception of facial taperness in Taiwanese females among people with dental knowledge and laypersons. Additionally, this study also specified the criteria by which "square face" was defined regarding Taiwanese females' facial taperness. Methods: A series of digitally modified photos with different levels of facial taperness (Gonion to Gonion/Zygoma point to Zygoma point—Go-Go/Zy-Zy ratio ranges from 65% to 90%) were randomly arranged and presented to the raters. Visual analog scale (VAS) lines were used for scoring the photos on a scale of 0–100. The true or false question about "defining square face" was incorporated in the same questionnaire. The reliability of the true/false square face question and the esthetic evaluation by VAS were assayed. The receiver operating characteristic curve was used to define the cutoff point on "square face." The effects on the raters' genders, orthodontic treatment experience, and their professional background on the perception of a square face were assayed. Results: The overall reliability of the raters was within the acceptable range. The VAS score evaluation revealed that the average expectation for best facial taperness was 75%, whereas the facial taperness of over 83% was considered as the square face. The facial taperness reaching to 90% was regarded as the most unattractive. Gender, therapy, and professional experience have no impact on the standard of square facial form evaluation. Conclusion: A face with a taperness greater than 83% was evaluated as a square face, and a face with a taperness around 75% was considered as the most attractive.